The use of unisexual wasps in biological control - Stouthamer, R (Quality Control and Production of Biological Control Agents, 2003)
Unisexual reproduction has long been seen as a clear advantage for wasps to be applied in biological control projects. The discovery that the mode of reproduction in parasitoid wasps may be manipulated from sexual to unisexual and vice versa will allow biocontrol workers to test the advantage of either mode of reproduction for biological pest control. Here a review is presented of the cases of unisexual reproduction found in parasitoid wasps. Unisexual reproduction is not rare among parasitoids; at least 150 cases of unisexual reproduction have been reported. The literature is reviewed for cases where both unisexual and sexual forms are used in the same control project to determine if the theoretical advantage of unisexual reproduction indeed materializes. Few cases can be used to test the presumed advantage of unisexuals. Some evidence is found for two advantages of unisexual reproduction: unisexuals are cheaper to produce in mass rearing than sexuals, and in classical biocontrol projects they are more easily established.